Mindfulness-Based Cognitive Therapy as a Treatment for Chronic Tinnitus: A Randomized Controlled Trial - McKenna,L; Marks,EM; Hallsworth,CA; Schaette,R (Psychotherapy and Psychosomatics, 2017)
Background: Tinnitus is experienced by up to 15% of the population and can lead to significant disability and distress. There is rarely a medical or surgical target and psychological therapies are recommended. We investigated whether mindfulness-based cognitive therapy (MBCT) could offer an effective new therapy for tinnitus. Methods: This single-site randomized controlled trial compared MBCT to intensive relaxation training (RT) for chronic, distressing tinnitus in adults. Both treatments involved 8 weekly, 120-min sessions focused on either relaxation (RT) or mindfulness meditation (MBCT). Assessments were completed at baseline and at treatment commencement 8 weeks later. The primary outcomes were tinnitus severity (Tinnitus Questionnaire) and psychological distress (Clinical Outcomes in Routine Evaluation - Non-Risk, CORE-NR), 16 weeks after baseline. The analysis utilized a modified intention-to-treat approach. Results: A total of 75 patients were randomly allocated to MBCT (n = 39) or RT (n = 36). Both groups showed significant reductions in tinnitus severity and loudness, psychological distress, anxiety, depression, and disability. MBCT led to a significantly greater reduction in tinnitus severity than RT, with a mean difference of 6.3 (95% CI 1.3-11.4, p = 0.016). Effects persisted 6 months later, with a mean difference of 7.2 (95% CI 2.1-2.3, p = 0.006) and a standardized effect size of 0.56 (95% CI 0.16-0.96). Treatment was effective regardless of initial tinnitus severity, duration, or hearing loss. Conclusions: MBCT is effective